Tradicija ali / in inovacija v arhitekturi - Zupančič-Strojan, Tadeja (Les (Ljubljana), 1999)
There is a hierarchy of polar concepts in architecture, usually representing separated and opposite categories. If one looks beyond the conventional distinctions the dynamic unity can be found that binds each pair together. One of these ambiguities, innovation (or modernity) and tradition (convention),could be found in the concepts of new and old, original and rooted, empirical and intuitive, rational and romantic, objective and relative, conscious and subconscious, universal and particular, mechanistic and organic, neutral and identical. The presented example of a traditional timber construction as a base of contemporary facade layers could indicate several possibilities in the search of dynamic equilibrium between the traditional spatial values and contemporary ubiety needs.
Keywords: architecture; arhitektura; tradicija; tradition; inovacije; identiteta; lesene zgradbe